Pengaruh Employe Engagement, Kepuasan Kerja, Stres Kerja serta Pengembangan Karir terhadap Turnover Intention pada Kepth Coffee Surabaya - Sipayung, Natalia Yustisia; Dewa Ketut Raka Ardiana; Sri Budi K; Endah Budiarti (Nirta Learning Centre, 2025)
Abstract. This study aims to prove and analyze the Influence of Employee Engagement, Job Satisfaction, Job Stress and Career Development on Turnover Intention on Kepth Coffee Surabaya Employees partially and simultaneously. The population in this study were 30 respondents or all employees of Kepth Coffee Surabaya. Data were collected through a questionnaire with a Likert scale as a measurement instrument. Data analysis techniques were carried out by validity testing, reliability testing, classical assumption testing, multiple linear regression testing, and T-test (partial) and F-test (simultaneous) to reveal the influence of Employee Engagement, Job Satisfaction, Job Stress and Career Development on Turnover Intention. Data analysis in this study used SPSS version 26. The results showed that all indicators of this study were valid and reliable. The results of this study indicate that only Job Stress (X3) has a significant influence on the Turnover Intention variable (Y). Other variables, namely Employee Engagement (X1), Job Satisfaction (X2), and Career Development (X4), did not show a significant influence partially on the Turnover Intention variable (Y) on Kepth Coffee Surabaya Employees. The results of the R² Test show that the influence of the independent variable on the dependent variable is 73.1% while the remaining 26.9% is influenced by other variables not explained in this study. Based on these findings, the limited number of respondents in this study was caused by access and time constraints, so it is recommended in further research to expand the reach, utilize digital platforms, or collaborate with related parties in order to obtain more representative data. Keywords : Employee Engagement, Job Satisfaction, Job Stress, Career Development, Turnover Intention